The journey to the promised land : the African American struggle for development since the Civil War - Mungazi, Dickson A. (Praeger, 2001)
A study of African American development since the Civil War, as measured by progress in four critical areas of national life: economic, political, educational and social. It includes discussion of important watershed events and key individuals who helped to redefine the nation's history.